Peran Guru PAUD Dalam Membangun Literasi Kesehatan: Studi Kasus Penerapan Hidup Sehat Pada PAUD Di Kecamatan Gunungpati - Nisak, Hanifatun; Rahayu, Sri Setiyo (Indonesian Journal of Health Community, 2025)
Health literacy is an important foundation in shaping healthy behaviors from an early age. This study aims to analyze the role of PAUD teachers in building healthy behaviors in early childhood in Gunungpati sub-district. The research used a qualitative with multiple-case design. The research subjects involved 30 teachers from 10 PAUD in Gunungpati Sub-district who were selected using purposive sampling technique. Data were collected through in-depth interviews, lesson observations, and documentation analysis. Data were analyzed using thematic analysis techniques with the stages of data reduction, data presentation, and conclusion drawing. The results showed that PAUD teachers act as learning facilitators, healthy behavior models, motivators, and health educators. Learning strategies carried out in this study include play-based learning activities, health storytelling, clean living habituation, and demonstration of healthy practices. Supporting factors for implementation include school commitment and children's enthusiasm, while inhibiting factors include limited teacher knowledge and lack of learning media. This study concludes that the role of PAUD teachers is very important in building early childhood health literacy, but requires increased competence and infrastructure support to achieve optimal results.